2022
DOI: 10.1021/acsinfecdis.2c00199
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Palmitoylation of Red Cell Membrane Proteins Governs Susceptibility to Invasion by the Malaria Parasite, Plasmodium falciparum

Abstract: Phosphorylation and other post-translational modifications of red blood cell (RBC) proteins govern membrane function and have a role in the invasion of RBCs by the malaria parasite, Plasmodium falciparum. Furthermore, a percentage of RBC proteins are palmitoylated, although the functional consequences are unknown. We establish dynamic palmitoylation of 118 RBC membrane proteins using click chemistry and acyl biotin exchange (ABE)-coupled LC−MS/MS and characterize their involvement in controlling membrane organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…In the current study, we comprehensively investigate the functional significance of the protease activity associated with Kell surface proteases and subsequently identified a highly effective, Kell-specific inhibitory compound. Our previous research demonstrated a substantial reduction in invasion efficiency upon exposure to Kell-specific antibodies 9 , underscoring a potential link between Kell and the invasion process. To comprehensively ascertain Kell's significance in the invasion, we adopted a CRISPR-Cas9-based approach to knockout the kell gene in an immortalized erythroid progenitor cell line, BEL-A 15 .…”
Section: Crispr-cas9 Mediated Kell Knockout In Bel-a Cell Line and It...mentioning
confidence: 57%
See 1 more Smart Citation
“…In the current study, we comprehensively investigate the functional significance of the protease activity associated with Kell surface proteases and subsequently identified a highly effective, Kell-specific inhibitory compound. Our previous research demonstrated a substantial reduction in invasion efficiency upon exposure to Kell-specific antibodies 9 , underscoring a potential link between Kell and the invasion process. To comprehensively ascertain Kell's significance in the invasion, we adopted a CRISPR-Cas9-based approach to knockout the kell gene in an immortalized erythroid progenitor cell line, BEL-A 15 .…”
Section: Crispr-cas9 Mediated Kell Knockout In Bel-a Cell Line and It...mentioning
confidence: 57%
“…In our pursuit of identifying erythrocytic proteases crucial for parasite invasion, we underscored the functional significance of the Kell blood group antigen 9 . Kell belongs to the neprilysin (M13) family of zinc endopeptidases and are the third most potent immunogenic system after ABO and Rh system [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we annotated 20 protein sequences having DHHC domains in Ld PATs for the first time, providing insight into their possible functions. Furthermore, we elucidated the significance of global palmitoylation in parasite growth and survival. , …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we elucidated the significance of global palmitoylation in parasite growth and survival. 13,20 In the current investigation, we combined in vitro parasitic based studies, in silico analysis, and biophysical assays to investigate the functional role of novel palmitoyl acyltransferase LdPAT6 in parasitic invasion and discovered a novel inhibitor against LdPAT6 for future chemotherapeutics. Employing a B2H assay approach, we discovered novel peptide inhibitors targeting the DHHC domain of LdPAT6, including a noteworthy 28-amino acid de novo peptide inhibitor denoted PS1 [Figure 2B(ii)].…”
Section: ■ Discussionmentioning
confidence: 99%
“…Site specific requirements of host cell proteins in malaria parasite invasion, development and host remodelling have been widely documented and postulated, with many as yet unidentified contributions undoubtedly still to be uncovered. These range from single nucleotide polymorphisms, sites of glycosylation ( Goerdeler et al., 2021 ) and palmitoylation ( Kumari et al., 2022 ) of receptors to phosphorylation sites within membrane and cytoskeletal adaptor proteins. By enabling their alteration (deletion, disruption or replacement with phospho-modification incompetent residues for example), immortalised erythroid cell lines allow for the role of such sites to be dissected within a true cellular context, providing a powerful tool for new mechanistic insight.…”
Section: Future Opportunitiesmentioning
confidence: 99%